HUBUNGAN ANTARA PENGALAMAN KERJA DAN TINGKAT PENDIDIKAN TERHADAP KINERJA PEGAWAI PADA DINAS KESEHATAN KOTA MATARAM - Khaerul Hadi; Laeli Kadarni (Sekolah Tinggi Ilmu Ekonomi AMM, 2018)
This study aims to determine the relationship between work experience and education level on employee performance at the health service of Mataram City. This research consists of 2 (two) variables that are independent variables work experience (X1), education level (X2) and also dependent variables of performance (Y). The number of population in this study as 91 people, the number of samples taken is the whole and samples taken use nonprobability sampling. Data were collected by interview/questionnaire, interview and documentation. The data obtained were analyzed with correlation data which was previously tested for validity and reliability. The result of this study indicate that the independent variables work experience that has a strong relationship /close with the value of coefficient 0,559<0,5 to dependent variable (performance) and level of education have weak relation to dependent variable (performance) because have coefficient value 2,11>0,5 on the staff of Mataram City health office.